Revision of Sthenelais Kinberg, 1856, Fimbriosthenelais Pettibone, 1971 and Eusthenelais McIntosh, 1876 (Polychaeta, Sigalionidae) in the Northeast Atlantic - Barnich, Ruth; Van Haaren, Ton (European Journal of Taxonomy, 2021)
Two common sigalionid species from the Northeast Atlantic, Sthenelais boa (Johnston, 1833) and S. limicola (Ehlers, 1864), have never been revised in detail. Although their validity has never been questioned, a number of taxonomic problems related to Sthenelais Kinberg, 1856 and the later established Fimbriosthenelais Pettibone, 1971 remain unresolved. The validity of F. minor (Pruvot & Racovitza, 1895) has been repeatedly discussed, but no agreement reached. Also the validity of Fimbriosthenelais has been at stake, affecting the generic assignment of Fimbriosthenelais zetlandica (McIntosh, 1876), another species present in the area. Among the investigated species of Sthenelais, some where thought to be synonyms of Eusthenelais hibernica McIntosh, 1876, which led us to also include Eusthenelais McIntosh, 1876. We also re-examined Eusthenelais abyssicola McIntosh, 1879, the only other species attributed to the genus, and confirm that it is indeterminable. In total, we investigated 37 nominal taxa reported from the Northeast Atlantic and as a result we consider only five species to be valid: Sthenelais boa, S. limicola, Fimbriosthenelais zetlandica, F. longipinnis (Grube, 1869) and Eusthenelais hibernica. These genera and species are described and discussed herein and an updated identification key to all Northeast Atlantic species of Sigalioninae Gonzalez et al., 2018 is given.